Getting to the Root of Plant Mineral Nutrition: Combinatorial Nutrient Stresses Reveal Emergent Properties. (June 2019) - Bouain, Nadia; Krouk, Gabriel; Lacombe, Benoit; Rouached, Hatem
Abstract : In nature, plants have to handle daily fluctuations in light and temperature. In addition, plants face biotic and abiotic stresses that often come in various combinations. For instance, the availability of various nutrients in soil is heterogeneous, resulting in combined nutrient stress. Recent studies reveal that plant responses to multiple nutrient stresses are not the summation of the plant responses to each individual stress. Here, we present and discuss the interactions between phosphate, nitrogen, and zinc to illustrate the effect of macro- and micronutrient interactions on plant growth and ion homeostasis. Solving the mystery of these interactions will pave the way to the development of strategies to improve crop productivity. Highlights: The plant ionome is the result of a complex interplay between nutrient availabilities. Plant root growth and development is modulated by nutritional crosstalk. Studying nutrient interactions reveals emergent properties. Plant responses to multiple-nutrient stress cannot be predicted from their responses to individual stress.